Penerapan LKPD Berbasis Project Based Learning (PjBL) Pada Materi Fluida Dinamis - Pandiangan, Jelita Anggriani; Hakim , Abd (Universitas Pendidikan Mandalika, 2025)
The background of this study stems from the unavailability of Project-Based Learning (PjBL) model-based Student Worksheets (LKPD) used in high school physics instruction. The objective of this research was to develop a PjBL-based LKPD for the Dynamic Fluids topic at SMA Negeri 14 Medan. This study employed a Research and Development (R&D) approach using the ADDIE development model. The research subjects included material experts, media experts, learning experts, and 36 students from class XI-1 of SMA Negeri 14 Medan. The instruments used consisted of validation questionnaires completed by experts, observation sheets, interviews, and pretest-posttest assessments. The findings revealed that the developed LKPD met the criteria of validity, with validation scores of 78% from material experts, 75% from media experts, and 79.1% from learning experts. In terms of practicality, the LKPD was rated very practical, with student assessments scoring 92.3% and teacher assessments scoring 90.2%. The effectiveness test, measured using normalized gain (N-gain), yielded a score of 0.77, categorized as high. Thus, it can be concluded that the Project-Based Learning (PjBL)-based LKPD developed in this study is valid, highly practical, and effective for use in physics education.